Various Elements of Heat Sources within an Optimized Photonic Crystal Vertical Cavity Surface Emitting Laser: Influence of Hole Etching Depth - Marjani, Saeid (Asian Journal of Chemistry, 2013)
In this work, the various elements of heat sources within the active region of a long-wavelength InGaAsP photonic crystal oxide vertical cavity surface emitting laser (VCSEL) at a constant bias power have been investigated. The device employs strain-compensated InGaAsP multi-quantum wells sandwiched between GaAs/AlGaAs and GaAs/AlAs distributed Bragg reflectors that are fused on both sides of the InP spacer. In this work, the etching depth was continued down to the top of lower InP layer while there was no hole in the previous work. This paper provides key results of the various elements of heat sources upon the hole etching depth, including the Joule heat power, the Peltier-Thomson heat power and the recombination heat power within the active region.